KEBIASAAN HIDUP SEHAT DAN STATUS GIZI PADA SISWA SEKOLAH DASAR: STUDI KASUS DI SDN TANDEK, JONGGAT, LOMBOK TENGAH - Hendry Budiawan; Johan Irmansyah; Indri Susilawati (Journal Sport Science, Health and Tourism of Mandalika (Jontak) e-ISSN 2722-3116, 2023)
This study aimed to evaluate the healthy living habits and nutritional status of students in grades IV and V at SDN Tandek, Jonggat, Central Lombok. A descriptive quantitative approach was used with a survey method. Data were collected using a closed-ended questionnaire adapted from Rezaldhi (2022). The analysis revealed that the majority of students exhibited adequate healthy living habits, but many still engaged in unhealthy practices, such as irregular eating habits and poor hygiene. Furthermore, students' nutritional status was found to be in the normal and underweight categories. These findings suggest the need for continuous efforts in fostering healthy habits and monitoring nutritional intake in students to promote their overall well-being.